Effects of nitrogen application rate and topdressing times on yield and quality of Chinese cabbage and soil nitrogen dynamics. Issue 1 (1st January 2019) - Qu, Zhao-ming; Qi, Xing-chao; Wang, Jing; Chen, Qi; Li, Cheng-liang
ABSTRACT: A good understanding of the relationship between vegetable quality and soil N balance is very important for proper nitrogen (N) management for crop productions. In this study, a field experiment was carried out to investigate the N application rate and times on Chinese cabbage yield and quality, N use efficiency, soil nitrate-N concentration, and soil pH. The experiment was implemented in a two-way factorial design and the two factors comprises of number of N applications (once, twice and three times, denoted as T1, T2 and T3) and N rates (15%, 30% and 45% less than conventional rates (CF), denoted as F1, F2 and F3, respectively). The treatments were also compared with a no-fertilizer blank and a control (CF) with a conventional N management practice. The results showed that the highest yield of cabbage (164.65 t hm −2 ), Vitamine C content (14.80 g 100 g −1 fresh mass), soluble sugar content (2.33 mg kg −1 ), plant N uptake (119.2 kg hm −2 ) were obtained under T3F1 treatment. Compared with CF treatment, T3F1 treatment significantly increased vegetable yield, vitamin C and soluble sugar content in fruit, and nitrogen use efficiency by 10.97%, 13.76% and 17.68%, and 18.76%, respectively. Nitrate-N content in cabbage was reduced by 7.55% in T3F1 treatment. With the reduced N application rate, soil pH gradually changed from 6.25 to 7.26. T3F1 treatment is a most suitable N management practice for vegetable production, in terms of higher vegetable yield and quality, soil N content, depressed soil acidification and nutrient uptake by Chinese cabbage.